Child abuse: will the doctor report? - Witold Pawłowski; Krzysztof Goniewicz; Mariusz Goniewicz; Dorota Lasota (Kazimierz Wielki University, 2018)
The phenomenon of child abuse is a very important social issue, not only globally, but also in Poland. There is a silent consent in the Polish society for violence against children. The research presents the issues of the children abuse issue and forms. The most important are: physical abuse, mental abuse, sexual abuse and negligence. Also research presents the legal instruments governing the obligation to report cases of violence against children including medical confidentiality It is still necessary to sensitize the doctors, and especially the paediatricians about the abused child issues, as well as to educate and broaden knowledge in the scope of recognizing such phenomena. The doctors' involvement and their will to act towards the social and legal direction, by helping the family and the child are also important. In the current situation, reporting of abuse cases and non-medical actions regarding this issue is mainly a moral and professional obligation of a doctor, coming mainly from the care about patient's health.